THE COMPATIBILITY OF BIG FIVE PERSONALITY TRAITS AND REFLECTIVE TEACHING AMONG IRANIAN EFL TEACHERS - Shabnam Alizadeh Incheh; Mahshad Tasnimi (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
During the recent decade, the slogan of reflective teaching has been embraced by teachers, teachers' educators, and educational teachers worldwide. Drawing on John Dewey's ideas, there are three attitudes of reflective teachers, i.e., open-mindedness, wholeheartedness, and responsibility. This study aimed to examine the relationship between the teachers' personality types and their teaching reflection elements. To this end, we asked 100 (aged 20 to 40; M = 29.30; SD = 3.60; 46% women) Iranian EFL teachers to complete the Big Five Inventory Personality Test and the Reflective Teaching Instrument. The results confirmed the hypothesis that each personality type correlated with elements of the teaching reflection. For instance, teachers with elevated Extrovertion were found to draw on the affective element in their teaching practices. The pedagogical implications of the findings are discussed